Simultaneous Chiral Resolution of Two Racemic Compounds by Preferential Cocrystallization. (6th August 2021) - Zhou, Fuli; Shemchuk, Oleksii; Charpentier, Maxime D.; Matheys, Chloé; Collard, Laurent; ter Horst, Joop H.; Leyssens, Tom
Abstract: We tap into an unexplored area of preferential crystallization, being the first to develop simultaneous chiral resolution of two racemic compounds by preferential cocrystallization. We highlight how the two racemic compounds RS ‐mandelic acid (MAN) and RS ‐etiracetam (ETI) can be combined together as enantiospecific R‐MAN⋅R‐ETI and S‐MAN⋅S‐ETI cocrystals forming a stable conglomerate system and subsequently develop a cyclic preferential crystallization allowing to simultaneous resolve both compounds . The developed process leads to excellent enantiopurity both for etiracetam ( ee >98 %) and mandelic acid ( ee ≈95 %) enantiomers. Abstract : Two racemic compounds are combined to form a stable conglomerate system. Both compounds are simultaneously resolved through a single preferential cocrystallization process, showing excellent enantiopurity towards both compounds.